THU0671 Standardised mortality rates for systemic lupus erythematosus in western australia from 1980 to 2015. (12th June 2018) - Raymond, W.D.; Preen, D.; Keen, H.; Inderjeeth, C.; Nossent, J.
Abstract : Background: Patients with Systemic Lupus Erythematosus (SLE) are at increased risk of premature mortality. However, population-level mortality rates for SLE have not yet been reported in Australia. Objectives: Calculate the standardised mortality rates (SMR) for SLE patients in Western Australia (WA) from 1980 to 2015, overall and by age and gender. Methods: Utilising whole-population linked hospital admission, cancer registration and death data for WA from 1980 to 2015, we compared characteristics and calculated SMRs (95% CI) for patients with SLE (ICD-9-CM 695.4, 710.0, ICD-10-AM L93.0, M32.0) against controls (5:1) free of rheumatic disease after matching for age, gender, Aboriginality and year of first SLE event. Results: SLE patients (n=2, 868) and controls (n=12, 785) recorded 1335 and 4400 deaths with crude mortality rates of 56.3/1, 000 vs 37.1/1, 000 person-years, respectively. SLE patients were approximately 10 years younger (71 vs 81 years) and 2.2-times more likely hospitalised at death (p<0.001). The age-adjusted SMR (per 1, 000) for SLE patients was 4.4 (95%CI 3.0, 5.8), and higher in females 5.4 (95%CI 3.5, 7.4) than in males 3.4 (95%CI 1.5, 5.4). Five-year period SMRs were 8.6 (95%CI 5.0, 12.2) between 1990–1994, 9.3 (95%CI 4.4, 14.2) between 1995–1999, 7.6 (95%CI 3.1, 12.1) between 2000–2004, 4.5 (95%CI 0.2, 8.7) between 2005–2009, and 4.9 (95%CI 1.32, 8.5) between 2010–2015. Conclusions: SLE patients in WA experienced a decline in SMRs over time, but remain at increased risk of premature mortality. Within the limitations of administrative linked data, SLE in WA associates with an average reduction in life span of 10 years. Acknowledgements: The authors wish to thank the staff at the Western Australian Data Linkage Branch and Emergency Department Data Collection, Hospital Morbidity Data Collection, WA Cancer Registry and Death Registrations. The Rheumatology Group of UWA (JN) was supported by an unrestricted grant from the Arthritis and Osteoporosis Foundation of Western Australia (AOWA). The AOWA provided WR with a PhD Scholarship in Memory of Johan Donald Stewart. This research was also supported by an unrestricted Australian Project Grant from Arthritis Australia. Disclosure of Interest: None declared